Civil Servants’ View of the Development of e-Government in Slovenia - Tina Jukić; Mateja Kunstelj; Mitja Dečman; Mirko Vintar (Central European Public Administration Review)
The paper presents the results of a study focused on the so-called internal aspect of e-government – i. e., the aspect of the civil servants. It is wellknown that in both Slovenia and most other countries there is a significant discrepancy between the selection and the actual use of the possibilities that e-government provides. A substantial number of researchers have been intensely engaged in the study of factors inciting (mainly) the citizens to use e-government. In our belief, those factors need also be searched for within the internal e-government users, i.e. the civil servants. In this perspective, we have examined: (1) their use of, and satisfaction with, information technologies in the job context; (2) their skills required for e-government; (3) the effect of e-government on their job, their organisation, and public administration in general; (4) their views of further development of e-government within the public administration. A number of results indicate that responsibility for the low use of e-government by citizens and enterprises can in fact be partly ascribed to the civil servants. Further, the research has revealed that the surveyed civil servants lacked sufficient skills required for an active participation in the development of e-government, and that this development has not resulted in any vital changes in the operations of the public administration.